Supplying UN Peacekeepers: An Assessment of the Body Bag Syndrome among OECD Nations. Issue 1 (1st January 2019) - Raes, Steffi; Du Bois, Cind; Buts, Caroline
ABSTRACT: The body bag syndrome is often described as a casualty aversion that decreases public support of participation in military missions. As policymakers believe in the body bag syndrome, they may adapt their foreign policy accordingly, leading to reduced willingness to supply personnel. This article seeks empirical evidence for the existence of the body bag syndrome, or the influence of casualties on the decision to remain engaged in a UN peacekeeping mission (PKO). A dataset containing all UN peacekeeping missions of OECD countries is set up for a period of 1996 to 2014, specifically focussing on decisions during ongoing missions. To capture the body bag syndrome, the casualties a country incurs during the previous year are included into an existing model for the supply of peacekeepers. The results show no evidence on the body bag syndrome for both the level of total casualties and casualties due to malicious acts, but casualties due to illnesses cause a reduction in personnel supplied to the mission. Other determinants which explain why countries remain engaged in a mission are mostly related to the conflict or the mission.